Nutrient utilisation and growth performance of rabbits fed diets based on maize, cassava or their by-products (1998)
A 70-day feeding trial was conducted to evaluate nutrient intake, digestibility and growth characteristics of rabbits fed maize grain (mg), maize offal (mo), cassava tuber (ct) or cassava peel (cp) based diets. The four test ingredients were included at 30.84% in diets supplying 17% crude protein. The consumption of dry matter, crude protein and crude fibre were higher (P4.05) in mo and cp based diets, while apparent digestibilities were better (Pc0.05) in rabbits fed mg and ct based diets. Rabbits fed mo attained the highest (P<0.05) body weight gain, followed by those fed mg and ct and the group fed cp gained the least. Feed consumption was higher (P<0.05) in rabbits fed cp and mo than mg and ct diets; and the gain: feed ratio was the reverse of the feed intake. It is concluded that mo and ct are effective substitutes for mg, however, diets based on cp would require nutrient supplementation.